The Influence Of Millennial Leaders’ Decision-Making Styles, Millennial Characteristics, And Work Period Toward Decision-Making Competence Case Study In Pt. Taspen (Persero) - putri ayu wulandari; Emilia Fitriana Dewi (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research analyzes the situation and conditions of  PT. Taspen (Persero) human resources which experiences generational differences between Baby Boomers and Millennials. This generational difference occurred because no employee recruitment existed between 1992 and 2006. On the other hand, as many as 163 employees will soon retire in 2024 to 2025. In other words, PT. Taspen (Persero) is dealing with employee shortages, especially in leadership positions. Therefore, PT. Taspen (Persero) has a very dynamic change of employee positions quickly. This causes Millennials to be prepared to become leaders within a minimum of 1.5 years after being appointed as permanent employees. Based on this, this research aims to examine the decision-making of Millennial leaders. Where in this case, the younger generation must be able to make the right decisions even though they have little experience and a short working time. Therefore, the researcher aims to know whether the natural characteristics possessed by Millennials as well as their work period and type of decision-making making will influence their competence in making decisions which will be assessed using the Adult Decision-Making Competence (A-DMC) model. On the other hand, company management, in this case, the human resources division, is also the object of research in qualitative form to find out how far management supports millennial leaders in decision-making by providing a conducive work environment.